Elimination of Lumbar Plexus Injury by Changing the Entry Point and Traction Direction of the Psoas Major Muscle in Transpsoas Lateral Lumbar Spine Surgery - Hidetoshi Nojiri; Takatoshi Okuda; Hiromitsu Takano; Motoshi Gomi; Ryosuke Takahashi; Arihisa Shimura; Shota Tamagawa; Takeshi Hara; Yukoh Ohara; Muneaki Ishijima (Medicina, 2023)
Background and Objectives: The lateral approach is commonly used for anterior column reconstruction, indirect decompression, and fusion in patients with lumbar degenerative diseases and spinal deformities. However, intraoperative lumbar plexus injury may occur. This is a retrospective comparative study to investigate and compare neurological complications between the conventional lateral approach and a modified lateral approach at L4/5. Materials and Methods: Patients with a lumbar degenerative disease requiring single-level intervertebral fusion at L4/5 were included and categorized into group X and group A. Patients in group X underwent conventional extreme lateral interbody fusion, while those in group A underwent a modified surgical procedure that included splitting of the anterior third of the psoas muscle, which was dilated by the retractor on the anterior third of the intervertebral disc. The incidence of lumbar plexus injury, defined as a decrease of ≥1 grade on manual muscle testing of hip flexors and knee extensors and sensory impairment of the thigh for ≥3 weeks, on the approach side, was investigated. Results: Each group comprised 50 patients. No significant between-group differences in age, sex, body mass index, and approach side were observed. There was a significant between-group difference in intraoperative neuromonitoring stimulation value (13.1 ± 5.4 mA in group X vs. 18.5 ± 2.3 mA in group A, p < 0.001). The incidence of neurological complications was significantly higher in group X than in group A (10.0% vs. 0.0%, respectively, p < 0.05). Conclusions: In our modified procedure, the anterior third of the psoas muscle was entered and split, and the intervertebral disc could be reached without damaging the lumbar plexus. When performing lumbar surgery using the lateral approach, lumbar plexus injury can be avoided by following surgical indication criteria based on the location of the lumbar plexus with respect to the psoas muscle and changing the transpsoas approach to the intervertebral disc.